Investigation of parameters of light characteristics of LED video screens of dynamic advertising equipment as factors influencing the human visual analyzer (Environment & Health, 2023)
The purpose of the work. Investigation of the physical characteristics of large geometric light video screens of dynamic advertising equipment as factors of possible adverse effects on visual analyzer of inhabitants of a surrounding housing.Results and discussion. Due to the development of outdoor advertising, the new generation of electronic panels can display video, multimedia, color, dynamic information, as well as quickly update advertising materials. This can cause an overload of the visual system and disrupt the normal functioning of brain, lead to visual fatigue. Studies of video screens on standardized parameters: lighting (lx), brightness (cd/m2) and non-standardized: lighting energy (mW/m2), color temperature (K), light pulsation (%) indicate their compliance with regulatory requirements of Ukraine and do not exceed levels regulated by other standards and recommended by the literature for sources of visible radiation. The exception is the angular size of the screen visible from the living room, which requires further studies.Conclusions. The use of geometrically large video screens of dynamic advertising equipment, especially in areas of dense housing and heavy traffic, requires improved methodological approaches to assessing the risks of visual discomfort and influence on public health.
Keywords: video screens; lighting; brightness; light pulsation; visual analyzer; public health